Papillon-Lefevre Syndrome: Challenge for Periodontal Management - Lamichhane, Krishna Prasad; Pradhan, Shaili; Gorkhali, Ranjita Shreshta; Koirala, Pramod Kumar (Journal of Nepalese Society of Periodontology and Oral Implantology, 2019)
Papillon-Lefèvre syndrome (PLS) is a rare autosomal recessive disorder associated with rapidly progressing periodontitis leading to premature loss of deciduous and permanent dentition and diffuse palmoplantar keratosis. Immunologic alterations, genetic mutations, and role of bacteria are some aetiologic factors. Patients present with early periodontal destruction, so periodontists play a significant role in diagnosis and management. This paper reports a case of Papillon- Lefevre syndrome with its clinical manifestations and challenges for periodontal management which was diagnosed in dental department.